2019
DOI: 10.3389/fnins.2019.00537
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Effect of Hemin and the Related Mechanism in Sevoflurane Exposed Neonatal Rats

Abstract: Background Many studies have reported that sevoflurane can increase neuronal apoptosis and result in cognitive deficits in rodents. Although neurotoxicity may be associated with mitochondrial dysfunction and oxidative stress, the exact mechanism remains unclear. In order to evaluate potential treatment therapies, we studied the effects of hemin on neurotoxicity of neonatal rat sevoflurane exposure. Methods Postnatal day (P) seven rats were assigned randomly to four grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 47 publications
3
14
0
Order By: Relevance
“…Our study found that the hippocampal synaptic protein was still lower when the sevoflurane-inhaled rats reached puberty (32 days of birth) ( Figure 2). This result was consistent with Mediators of Inflammation our previous research and other literature reports [15][16][17][18]. We found that preinjection of dexmedetomidine before sevoflurane exposure can alleviate the decline of long-term hippocampal synaptic protein SYP and PSD95 after sevoflurane anesthesia, suggesting that the protection of dexmedetomidine can last for long term.…”
Section: Dexmedetomidine Alleviated the Decline In Learning Andsupporting
confidence: 93%
“…Our study found that the hippocampal synaptic protein was still lower when the sevoflurane-inhaled rats reached puberty (32 days of birth) ( Figure 2). This result was consistent with Mediators of Inflammation our previous research and other literature reports [15][16][17][18]. We found that preinjection of dexmedetomidine before sevoflurane exposure can alleviate the decline of long-term hippocampal synaptic protein SYP and PSD95 after sevoflurane anesthesia, suggesting that the protection of dexmedetomidine can last for long term.…”
Section: Dexmedetomidine Alleviated the Decline In Learning Andsupporting
confidence: 93%
“…Following the study of Amrock et al, some researches focus on the expression changes of mitochondrial fission and fusion proteins. These researches found that sevoflurane induces the upregulation of Drp1 and Fis1 and the downregulation of Mfn2 and Opa1 [ 26 , 27 , 40 , 73 ]. It seems that sevoflurane could disturb the balance of mitochondrial dynamics through promoting mitochondrial fission and suppressing mitochondrial fusion, thereby inducing the damage of neural cells.…”
Section: The Involvement Of Mitochondrial Dynamics Imbalance In Nementioning
confidence: 99%
“…Hemin was also recently described to exert neuroprotective effects via abrogation of sevoflurane-induced activation of the mitochondrial intrinsic pathway of apoptosis [40]. This was discussed to be mediated via induction of neuroglobin levels; however, CO signaling following hemin degradation by heme oxygenases was not excluded as the mode of action.…”
Section: Discussionmentioning
confidence: 99%